ANFIS Based Approach to Estimate Remnant Life of Power Transformer by Predicting Furan Contents - Priyesh Kumar Pandey; Zakir Husain; R K Jarial (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Condition monitoring and diagnostic playing important role in estimating remnant Life of power transformer. Concentration of furan content in transformer oil can be a promising factor for indirect measurement of the aging of transformer insulation. The oil gets contaminated mainly due to prolonged operation and ageing. The present research paper introduces Adaptive Neuro Fuzzy inference system (ANFIS) technique to correlate furanic compounds obtained by High Performance Liquid Chromatography (HPLC) test to remnant life of the power transformer. The results are obtained by conducting HPLC test at TIFAC-CORE lab, NIT Hamirpur on thirteen samples of Power transformer oil taken from Himachal State Electricity Board Ltd, Shimla (India).DOI:http://dx.doi.org/10.11591/ijece.v4i4.5567